ANALISIS FAKTOR PENYEBAB KEGAGALAN PENCAIRAN DANA KREDIT USAHA RAKYAT ( KUR ) DI BANK BTN KCP WONOSOBO - Devi Novita Sari; Atika Atika (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2025)
Bank Tabungan Negara (BTN) KCP Wonosobo is a state-owned bank committed to supporting national economic growth through various financing products, one of which is the People's Business Credit (KUR). KUR BTN is a financing program designed for Micro, Small, and Medium Enterprises (MSMEs) that require business capital with low interest rates and easier requirements. This product aims to expand financing access for MSMEs, stimulate real sector growth, and create more job opportunities. Through KUR, Bank BTN actively contributes to strengthening financial inclusion, offering competitive capital solutions, and supporting the sustainability of small and medium enterprises in Indonesia. This research aims to identify the factors that lead to the failure of KUR fund disbursement at Bank BTN KCP Wonosobo. The study adopts a qualitative approach and conducts a comprehensive analysis of the issue. The research sources consist of primary and secondary data obtained from interviews and data observations. The results of this study conclude the various factors that prevent the disbursement of KUR loan funds, whether due to bank regulations or borrower- related issues.